Active control of terahertz plasmon-induced transparency in the hybrid metamaterial/monolayer MoS2/Si structure. Issue 19 (30th April 2019) - Ji, Jie; Zhou, Siyan; Wang, Weijun; Ling, Furi; Yao, Jianquan
Abstract : Active control of terahertz waves is critical to the development of terahertz devices. In this study, we investigated modulation property of terahertz wave based on the hybrid metamaterial/monolayer MoS2 /Si structure with tunable infrared light. Abstract : Active control of terahertz waves is critical to the development of terahertz devices. Two-dimensional materials with excellent optical properties provide more choices for opto-electrical devices due to the advancement in their preparation technology. We proposed a hybrid structure of a metamaterial/monolayer MoS2 /Si and investigated its optical properties in the terahertz range. The plasmon-induced transparency (PIT) effect was observed in the transmission spectra, resulting from the near-field coupling of two bright modes. According to the simulated results, this phenomenon confirmed its dependency on the length of the cutwire and the distance between DSSRs. Furthermore, an external optical field supported by a 1064 nm laser could exert a switch effect on the sample. The resonances of the PIT metamaterial disappeared when the optical power was further increased, as the excited carriers in the MoS2 /Si substrate blocked the coupling effect. In addition, the experimental results indicated that the PIT metamaterial enhanced the interaction of infrared light with the monolayer MoS2 /Si substrate.